Permissive hypercapnia in ventilated preterm infants: when is it safe to perform? - Sabina Terzic; Suada Heljic; Naris Pojskic; Edo Hasanbegovic (Hygeia Press di Corridori Marinella, 2017)
Introduction: In spite of measures to avoid invasive mechanical ventilation, many preterm infants are still artificially ventilated. The need for intubation and positive pressure ventilation is associated with so-called ventilator-induced lung injury (VILI) and bronchopulmonary dysplasia (BPD). A lot of strategies are made in order to minimise VILI. One of these strategies is the use of permissive hypercapnia, in which clinicians use more gentle ventilatory strategies and accept higher than "normal" alveolar partial pressure of carbon dioxide (PaCO2) values. Although there are promising studies about the use of permissive hypercapnia in preterm infants, we are still not sure if and when this mode of treatment is safe. Aim: The aim of this study is to investigate conditions in which permissive hypercapnia is safe to prematurely born infants regarding their survival. Methods: The present study was conducted in a tertiary research and educational hospital, NICU, Pediatric Clinic, Clinical Center University of Sarajevo (Sarajevo, Bosnia and Herzegovina). All infants had chest X-ray at admission, and were treated for respiratory distress syndrome (RDS) with nasal continuous positive airway pressure (nCPAP), conventional mechanical ventilation (CMV), or high frequency oscillatory ventilation (HFOV). At admission we registered data regarding birth weight (BW), gestational age in weeks (GW), Apgar score and prenatally given steroids. Inclusion criteria were fulfilled by 200 infants. According to their mean PaCO2, patients were divided into hypercapnia and normocapnia groups. We analyzed the outcome (survival) of these two groups. Results: The two groups didn't differ regarding GW, prenatally given steroids, RDS severity, surfactant use, 1- and 5-minute Apgar score, nor according to their CRIB score. Groups had also similar survival. After performing ROC analysis we have found that infants born ≤ 27 GW and ≤ 1,000 g treated with permissive hypercapnia, and infants with normocapnia born ≤ 26 GW and ≤ 980 g, have a prediction of negative outcome regarding survival, with a high level of accuracy. Conclusions: This study shows that ventilation with permissive hypercapnia of preterm infants with RDS is not safe, considering survival in children with GW ≤ 27 and BW ≤ 1,000 g.